Survivability of Lactobacillus plantarum in nutmeg (Myristica fragrans Houtt) flesh extract and its effect on the performance of broiler chicken (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study aimed to see if increasing the concentration of nutmeg flesh extract in vitro could increase the growth of Lactobacillus plantarum bacteria and if it had any effect on broiler chicken performance. Materials and Methods: Different concentrations of nutmeg flesh extract (5, 10, 15, and 20/100 ml distilled water) were combined with 10 ml L. plantarum (bacterial concentration 1 × 109 cfu/ ml) to produce synbiotics. A total of 250 unsexed Lohmann broiler chickens were reared together from 0 to 7 days of age in the in vivo study. Beginning on day 8, synbiotics nutmeg flesh extract and L. plantarum were added to the ration in amounts of 0.5, 1, 1.5, and 2 ml/kg for T1, T2, T3, and T4, respectively, while no synbiotics were added to the control diet (T0). Results: The levels of nutmeg flesh extract had a significant (p < 0.05) effect on L. plantarum growth. In the survival test against gastric acid, bile salts, and temperature, the addition of nutmeg flesh extract (20/100 ml distilled water) significantly (p < 0.05) maintained the population of L. plantarum. In vivo studies showed that the T1,T2,T3, and T4 groups gained more body weight (p < 0.05) than the T0 group during the rearing period but had no effect (p > 0.05) on the internal organ weight and carcass of broiler chickens. Conclusions: Nutmeg flesh extract could stimulate the growth of L. plantarum bacteria, and using it as a synbiotic could improve broiler chicken performance.J. Adv. Vet. Anim. Res., 10(1): 42–50, March 2023http://doi.org/10.5455/javar.2023.j650